The effect of Kappaphycus alvarezii active fraction on oxidative stress and inflammation in streptozotocin and nicotinamide-induced diabetic rats - Yulianti, Evy; Sunarti, Sunarti; Wahyuningsih, Mae Sri Hartati (BioMed Central Ltd, 2022)
Background: High glucose concentration increases the glycation process which leads to oxidative stress and inflammation, that can cause complications in diabetes. Several medicinal plants have been used in the treatment of diabetes and its complications. One of them is Kappaphycus alvarezii, an algae that has known antidiabetic abilities. This study aimed to examine the effect of K. alvarezii active fraction on plasma hydrogen peroxide (H2O2) and Tumor Necrosis Factor α (TNFα) levels, renal NADPH oxidase 4 (NOX4) and Nuclear Factor κ B (NFκB) gene expressions. Methods: Active fraction was obtained from bioassay-guided fractionation with antiglycation ability. In vivo study was performed on twenty Wistar male rats. The level of H2O2 was measured using H2O2 Assay Kit, the Optical Density value measured using spectrophotometer at a wavelength of 405 nm. Plasma TNFα level was measured using ELISA. Renal NOX4 and NFκB gene expression was analyzed using qPCR. Results: Active fraction significantly reduced plasma H2O2 but not TNFα levels. Furthermore, renal NOX4 gene expression was lower in the diabetic rat group treated with active fraction compared to the untreated group but not NFκB gene expression. Conclusions: K. alvarezii active fraction has an activity to reduce plasma H2O2 as well as renal NOX4 gene expression. Therefore, this fraction could be developed as a potential candidate for diabetes treatment through oxidative stress mechanisms. © 2022, The Author(s).